Antagonism against Listeria spp. and Staphyloccocus aureus by bacteriocin-producing lactic acid bacteria screened from the intestine of Philippine carabao, using polymerase chain reaction - Elegado, Francisco B.; Abuel, Butch Josef A.; Te, Johnston T., Jr.; Calapardo, Marilou R.; Parungao, Marilen M. (2007)
Lactic acid bacteria, isolated from the small intestine of the Philippine water buffalo or carabao (Bubalus bubalis L.), were screened for pediocin and plantaricin genes, using polymerase chain reaction. Out of 14 lactic acid bacteria found positive for the bacteriocin-encoding genes, only four were confirmed bacteriocinogenic, identified as: Lactococcus lactis K3a2-2, Pediococcus pentosaceous K2a2-3 and Pediococcus acidilactici K2a2-1 and K2a2-5, using API-50 CHL® ID kit. The antimicrobial activities of the growing cells and the bacteriocin activities of the cell-free, pH-neutralized culture supernatants of these four new isolates were compared with those of three fermented food isolates which have been previously studied - P. acidilactici S3, P. acidilactici AA5a and Lactobacillus plantarum BS - and were assayed against five Listeria spp. and five Staphylococcus aureus strains. All bacteriocinogenic lactic acid bacteria were antagonistic against the indicator organisms. On the other hand, four Listeria spp. strains and only one S. aureus strain (PNCM 1976) were inhibited by bacteriocins produced by the lactic acid bacteria (LAB) isolates. P. acidilactici K2a2-1, the lactic acid bacterium from the intestine of the Philippine carabao, which showed the highest bacteriocin activity, was partially purified by pH adsorption-desorption method for partial characterization of its inhibitory activity against Listeria monocytogenes and Staphylococcus aureus PNCM 1976 at various conditions. Bacteriocin exhibited optimum activity at pH 5-7. However, activity was lost with protease treatment and decreased slightly with amylase treatment, indicating P. acidilactici K2a2-1 bacteriocin as proteinaceous with hints of glyco-moiety. Boiling for 5-30 min resulted in decreased bacteriocin activity against L. monocytogenes but not against S. aureus PNCM 1976. Bacteriocin activity was totally lost when autoclaved for 15 min at 15 psi. The minimum inhibitory concentration (MIC) was observed at 12.5% and 25% dilution of the partially purified bacteriocin against 3 Log CFU mL-1 of L. monocytogenes and S. aureus PNCM 1976, respectively.
Keywords: Lactic acid bacteria